Digital Currency Between Emerging Crimes and Countermeasure Strategies - Isniba, Abdullah Al-Sharif Ahmed (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
The development of digital currencies (cryptocurrencies) based on blockchain technology has brought significant changes in the global financial system while giving rise to new forms of transnational crime. On the one hand, digital currencies offer efficiency and innovation in financial transactions, but on the other hand, they pose legal risks in the form of money laundering, terrorism financing, and cybercrime. This research aims to analyze the position of digital currencies as a medium of modern crime and examine its countermeasures from the perspective of positive law and Islamic law. The research method used is descriptive-analytical with a normative approach through the study of laws and regulations, religious fatwas, international documents, and contemporary legal literature. The results show that the characteristics of digital currencies that are decentralized, anonymous, and cross-border make them vulnerable to abuse for illegal activities. From the perspective of Islamic law, digital currencies are still the object of debate, especially related to the elements of gharar, maysir, and the potential of mafsadah, so the assessment is highly dependent on its function, mechanism of use, and legal impact on the public good.